Production and consumption of news for smart speakers in Brazil: Patterns and challenges in the covid-19 pandemic - Crespo, M.; Andrade, W. (Proceedings of the IWEMB 2021 and 2022, 2023)
A smart speaker is a small speaker with a microphone installed, without a keyboard, to be operated only by the user's voice, which is an interface very different from more traditional ones (writing or touching). The device may or may not have a screen, but smart speakers without a screen are the most popular. The smart speaker market has also been impacted by the covid-19 pandemic. The global market is estimated to grow from $4.66 billion in 2020 to $6.98 billion in 2021, at a compound annual growth rate (CAGR) of 49.8%. Avaliable in Brazilian Portuguese since 2018, these devices saw an increase in usage in Brazil between 2020-2021, compared to previous years. In this research we used mixed methods in our investigation because it employs a strategy of inquiry involving either the simultaneous or sequential collection of data and collects both numeric information and text information. We used two methodological techniques: an online survey, interviews, and online thematic analysis. We needed these techniques to understand how the consumer uses voice assistants, what journalism companies are developing content to these devices, and to analyse data from technology companies' reports. To understand the challenges and advantages from both the consumer and the content producer side in this new world of voice interaction devices, we applied a survey to 112 Portuguese-speaking smart speaker users, and interviewed three Portuguesespeaking content producers, two of them from the largest media companies in Portuguese. We cross-referenced the survey and interview data and were able to discern a pattern of news consumption through smart speakers.